The effect of financial literacy, financial inclusion knowledge, and the Tamansiswa teaching "Opor Bebek Mateng Soko Awake Dewe" on the development of Wedang Uwuh MSMEs in Bantul Regency - Pangestu, Mateus Ivano Nico Wijaya (Proceeding International Conference on Accounting and Finance, 2024)
This research aims to analyze the influence of financial literacy, knowledge of financial inclusion and Tamansiswa's teaching "Opor Bebek Mateng Soko Awake Dewe" on the development of wedang uwuh micro, small and medium enterprises (MSMEs) in Bantul Regency. This research uses a quantitative approach using primary data. The population in this study was wedang uwuh MSMEs in Bantul Regency and the sample was 107 respondents. Sampling was taken using random sampling and data was processed using IBM SPSS 25. The research independent variables were financial literacy, knowledge of financial inclusion and the Tamansiswa teaching "Opor Bebek Mateng Soko Awake Dewe", while the development of MSMEs in Bantul Regency was the dependent variable. The results of this research explain that financial literacy, knowledge of financial inclusion have a positive effect on the development of wedang uwuh MSMEs in Bantul Regency, while Tamansiswa's teaching " Opor Bebek Mateng Soko Awake Dewe" has no effect on the development of wedang uwuh MSMEs in Bantul Regency.